SHM_415396_HST_3D Boat Axe Type E:1 (Vellinge 1) - Qallaki, Ylber; Strandberg, Caroline; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Middle Neolithic stone boat axe type E:1 (Vellinge 1) collected from Hajom parish in Västra Götaland and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=689

Link to Sök I Samlingarna

https://samlingar.shm.se/object/C7731AAC-575D-4529-8D90-D28ED3524862
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; History and archaeology; Archaeology/history; Dynamic Collections; Hajom; Swedish Middle Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi